Dual expression and anatomy lines allow simultaneous visualization of gene expression and anatomy. Issue 1 (29th October 2021) - Kümpers, Britta M C; Han, Jingyi; Vaughan-Hirsch, John; Redman, Nicholas; Ware, Alexander; Atkinson, Jonathan A; Leftley, Nicola; Janes, George; Castiglione, Giuseppe; Tarr, Paul T; Pyke, Kevin; Voß, Ute; et al.
Abstract: Studying the developmental genetics of plant organs requires following gene expression in specific tissues. To facilitate this, we have developed dual expression anatomy lines, which incorporate a red plasma membrane marker alongside a fluorescent reporter for a gene of interest in the same vector. Here, we adapted the GreenGate cloning vectors to create two destination vectors showing strong marking of cell membranes in either the whole root or specifically in the lateral roots. This system can also be used in both embryos and whole seedlings. As proof of concept, we follow both gene expression and anatomy in Arabidopsis ( Arabidopsis thaliana ) during lateral root organogenesis for a period of over 24 h. Coupled with the development of a flow cell and perfusion system, we follow changes in activity of the DII auxin sensor following application of auxin. Abstract : A vector system and flow cell set-up allow long-term imaging of both gene expression and anatomy in Arabidopsis primary and lateral roots.